Enhancing operational efficiency and financial reporting through Oracle NetSuite ERP implementation: A case study in a logistics company - Stepani Sisca Wulandari; Kevin Maulana (International Research Journal of Science, Technology, Education, and Management)
The objective of this study is to investigate the outcomes of implementing Oracle NetSuite, an Enterprise Resource Planning (ERP) software, in a logistics company located in Indonesia. This research presents a case study that examines the implementation of Oracle NetSuite to reengineer business processes within the company. Employing a descriptive research approach, this study explores the specific context of the business process redesign in one of the logistics companies in Indonesia as a case study for utilizing Oracle NetSuite ERP, which can provide valuable insights for future research. The data for this study was collected through semi-structured interviews, observation, and documentation analysis. The findings reveal that "Logistics Company" utilizes various modules such as Procure to Pay, Inventory, Fixed Asset, and General Ledger within the ERP Oracle NetSuite system to generate financial reports for the company. In addition, the study focusing on the complications faced during transaction recording. The structure of the IT department in "Logistics Company" and the application of Oracle NetSuite software for financial reporting are both detailed. The study highlights the benefits and challenges associated with implementing ERP systems, emphasizing the importance of aligning the chosen ERP system with the organizational functionalities, culture, strategy, and structure. Also, the modules within Oracle NetSuite, including Procure To Pay, Inventory, Fixed Asset, and General Ledger, are explained, along with their respective functionalities. The research concludes by emphasizing the importance of Oracle NetSuite in effectively handling financial transactions and producing reports for the "Logistics Company”. The complexities of ERP projects and the need for thorough readiness processes are also explored, suggesting solutions for effective ERP implementation. The adoption of Oracle NetSuite ERP significantly benefits "Logistics Company" in its day-to-day operations and facilitates the preparation of financial reports.